2018
DOI: 10.1055/s-0038-1675687
|View full text |Cite
|
Sign up to set email alerts
|

Noncompliance to Diet and Medication among Patients with Type 2 Diabetes Mellitus in Selected Hospitals of Kathmandu, Nepal

Abstract: Background Diabetes is a major public health problem affecting people of all ages globally. Noncompliance compromises the effectiveness of treatment and adversely affects patients' health. The main purpose of this study was to assess and compare the proportion of noncompliance to diet and medication between patients with type 2 diabetes mellitus (T2DM) visiting public and private hospitals in Kathmandu, Nepal. Methods Descriptive cross-sectional study was conducted in T2DM patients visiting public an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 26 publications
4
8
2
Order By: Relevance
“…Contrary to our expectations, the majority of T2DM patients (60.7%) in our study reported poor dietary compliance despite good nutritional knowledge. This is consistent with those from similar single-site studies in Komotini, Greece (Katsaridis et al, 2020), Eastern Ethiopia (Mohammed et al, 2020, Kampala, Uganda (Davidsson & Fahlén, 2016), Kathmandu, Nepal (Kafle et al, 2018), northwest Ethiopia (Ayele et al, 2018), and Kelantan, Malaysia (Tan et al, 2011) where 58.8%, 62.5%, 53.3%, 91.2%, 74.3%, and 83.6% of T2DM patients, respectively were non-adherent to dietary recommendation provided by their dieticians. A possible explanation for the poor dietary compliance despite good nutritional knowledge is the fact that several factors other than nutritional knowledge influence individuals' food selection and dietary habits, including psychosocioeconomic factors such as work-related barriers, community-level, and organizational barriers, personal challenges, and other factors (Shamsi et al, 2013) patients' adherence to recommended dietary practices, it is important that nutritionists and dieticians adopt dietary interventions tailored to patient's readiness to change, employing relevant behavioural change communication skills such as Transtheoretical Model (Tan et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Contrary to our expectations, the majority of T2DM patients (60.7%) in our study reported poor dietary compliance despite good nutritional knowledge. This is consistent with those from similar single-site studies in Komotini, Greece (Katsaridis et al, 2020), Eastern Ethiopia (Mohammed et al, 2020, Kampala, Uganda (Davidsson & Fahlén, 2016), Kathmandu, Nepal (Kafle et al, 2018), northwest Ethiopia (Ayele et al, 2018), and Kelantan, Malaysia (Tan et al, 2011) where 58.8%, 62.5%, 53.3%, 91.2%, 74.3%, and 83.6% of T2DM patients, respectively were non-adherent to dietary recommendation provided by their dieticians. A possible explanation for the poor dietary compliance despite good nutritional knowledge is the fact that several factors other than nutritional knowledge influence individuals' food selection and dietary habits, including psychosocioeconomic factors such as work-related barriers, community-level, and organizational barriers, personal challenges, and other factors (Shamsi et al, 2013) patients' adherence to recommended dietary practices, it is important that nutritionists and dieticians adopt dietary interventions tailored to patient's readiness to change, employing relevant behavioural change communication skills such as Transtheoretical Model (Tan et al, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, more than half of the respondents were non-adherent to dietary recommendations. There seem to be similarities between the dietary adherence found in the current study and those reported in similar single-site studies in Ghana ), Greece (Katsaridis et al, 2020, and Nepal (Kafle et al, 2018). Seasonal food shortages occur in Ghana, particularly in the Northern part of the country, from March to June (Agble et al, 2009).…”
Section: Discussionsupporting
confidence: 83%
“…In a global context, diabetes medication adherence has been associated with the female gender [ 17 ], level of education [ 18 , 19 ], knowledge about diabetes [ 18 , 19 ], duration of diabetes [ 19 , 20 ], perception of disease severity [ 17 ], among other factors. In Nepal, few studies have identified factors for the adherence or non-adherence to treatment among patients with type 2 diabetes [ 21 , 22 , 23 , 24 , 25 ]. The good medication adherence measured using the eight-item Morisky medication adherence scale (MMAS-8) was 28.5% in Nepal [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for non-adherence were intentional discontinuation, forgetfulness, carelessness, and hypoglycemia [ 22 ]. However, these previous studies have used simple statistical methods to determine predictors of medication adherence [ 21 , 22 , 24 , 25 ]; only one used multiple logistic regression [ 23 ]. Two studies used MMAS-8 [ 21 , 25 ], two studies used MMAS-4 [ 23 , 24 ], one study did not use standardized questions to measure medication adherence and failed to identify its associated factors scientifically [ 22 ].…”
Section: Introductionmentioning
confidence: 99%